2021
DOI: 10.1080/16878507.2021.1957398
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor impact of iron oxide nanoparticles in Ehrlich carcinoma-bearing mice

Abstract: Magnetic nanoparticles are promising approaches for cancer treatment. Iron oxide nanoparticles have been pre-formed by the co-precipitation method to investigate their antitumor activity on Ehrlich carcinoma in mice. The nanoparticles have been studied by UV spectrophotometer, transmission electron microscopy, dynamic light scattering, and zeta potential measurement. To determine the therapeutic impact of Iron oxide nanoparticles in tumorbearing mice, in vivo experiments were carried out. Fourier Transform Inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…After incorporating Aloe vera into Cs-Mxd NPs, it was clear that both the absorption band at 1727 cm −1 , due to C=O stretching (which indicates the presence of carbonyl groups in Aloe vera), and the absorption peak at 1255 cm −1 , corresponding to the C-O stretching of -COCH 3 groups, had totally disappeared [46]. By comparing the FTIR spectra of Cs-Mxd NPs before and after Aloe vera incorporation, it was found that absorption peaks at 1381, 962, and 865 cm −1 disappeared, proving that Aloe vera was incorporated successfully in the prepared drug carrier [47].…”
Section: Characterisation Of the Nanocompositesmentioning
confidence: 90%
“…After incorporating Aloe vera into Cs-Mxd NPs, it was clear that both the absorption band at 1727 cm −1 , due to C=O stretching (which indicates the presence of carbonyl groups in Aloe vera), and the absorption peak at 1255 cm −1 , corresponding to the C-O stretching of -COCH 3 groups, had totally disappeared [46]. By comparing the FTIR spectra of Cs-Mxd NPs before and after Aloe vera incorporation, it was found that absorption peaks at 1381, 962, and 865 cm −1 disappeared, proving that Aloe vera was incorporated successfully in the prepared drug carrier [47].…”
Section: Characterisation Of the Nanocompositesmentioning
confidence: 90%
“…As a continuation of our interesting research in evaluation of therapeutic potential drugs of medical importance, we report herein, a facile route to prepare a new nano-formula for gallic acid and evaluate its preventive efficacy against LPS-induced lung fibrosis in rats.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles account for nanoscale applications, providing a high surface area and efficient interaction, and working as carriers for molecules. , Nanoparticles can be selectively used to target the delivery of therapeutic drugs and decrease drug resistance by cancer cells . Niosomes are distinctive drug nanocarriers developed by non-ionic surfactants and cholesterol self-association in an aqueous solution .…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 7 Nanoparticles can be selectively used to target the delivery of therapeutic drugs 8 and decrease drug resistance by cancer cells. 9 Niosomes are distinctive drug nanocarriers developed by non-ionic surfactants and cholesterol self-association in an aqueous solution. 10 They can encapsulate hydrophilic and hydrophobic drugs with adequate efficiency.…”
Section: Introductionmentioning
confidence: 99%